Media pembelajaran komik digital tema kemerdekaan muatan ilmu pengetahuan sosial bagi siswa sekolah dasar - Fraftasari , Fraftasari; Andini, Dinar Westri; Azizah, Dinar Martia (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2024)
This research aims to: (1) Develop digital comic media in Social Science subjects of grade V SD Negeri Rejowinangun 1 Yogyakarta, (2) Test the feasibility of digital comic media in Social Science subjects of grade V SD Negeri Rejowinangun 1 Yogyakarta.  This research is a Research and Development (R&D) research, using the ADDIE development model. There are 5 (five) development steps, namely analysis, design, development, implementation, and evaluation. The population in this study were fifth grade students at Rejowinangun 1 Yogyakarta State Elementary School, totaling 26 students. Meanwhile, the sample was taken from teachers and fifth grade students as many as 10 students. The procedure for developing digital comic media in Social Studies subjects for grade V students refers to Analysis, Design, Development, Implementation, and Evaluation (ADDIE). Based on the results of the questionnaire by media expert validation, the average is 94.5% so that it is included in the "Very Feasible" category. Based on the validation of material experts, it gets an average of 92.5% "Very Feasible". Based on the results of the teacher response questionnaire, it gets a value of 94.44% so that it is included in the "Very Feasible" category. Based on the results of the questionnaire responses of students get a value of 96.25% so that it is included in the "Very Feasible" category. Based on the following results, it shows that digital comic media is very feasible to use in learning activities in grade V SD.